Lord Charles Somerset and the 'Beaufort influence' - Roberts, Michael,1908-1996; Van Niekerk, Melt; Young, Lindsay; Rossouw, P. J (Stellenbosch : Stellenbosch University, 2012)
Rossouw's contribution originally approved as M.A. thesis at the University of Stellenbosch.